Consumo de luxo em São Paulo: um estudo sobre o Shopping Cidade Jardim - Gazurek, Marie-Océane (2011)
This dissertation has for objective to investigate the meaning of luxury consumption in Shopping Cidade Jardim, a shopping center located in an affluent condominium in the western district of São Paulo. The initial working hypothesis states that those who seek to consume there do so as a means of establishing, and/or reinforcing, relations based upon social distinction. The study begins with a bibliographical debate over the meaning of consumption, led by the following authors opuses: Pierre Bourdieu, Jean Baudrillard, Grant McCracken, Baron Isherwood, Mike Featherstone, Heitor Frúgoli Jr., Valquíria Padilha and Gilles Lipovestky, while such concepts as cultural capital new taste maker , identity construction , hedonism and experience are also reviewed and debated. In a second moment, a discussion over the dynamics of luxury consumption through time is then presented. After contextualizing the construction of Shopping Cidade Jardim within the changes in the city of São Paulo, an ethnographic observation of the shopping, a series of consumer interviews, as well as an analysis of the Cidade magazine are henceforth presented. This analysis affirms that those who consume at Shopping Cidade Jardim go there to claim their belonging to the Paulistana elite and to a lifestyle - that is idealized in Cidademagazine characterizing a world of luxury goods, events and travel. Social distinction is not only sought after between varying groups, but also within their own group, by demonstrating the ownership of incorporated cultural capital